2008
DOI: 10.1042/bj20080543
|View full text |Cite
|
Sign up to set email alerts
|

Growth of β2-microglobulin-related amyloid fibrils by non-esterified fatty acids at a neutral pH

Abstract: Abeta2M (beta(2)-microglobulin-related) amyloidosis is a frequent and serious complication in patients on long-term dialysis. Partial unfolding of beta2-m (beta(2)-microglobulin) may be essential to its assembly into Abeta2M amyloid fibrils in vivo. Although SDS around the critical micelle concentration induces partial unfolding of beta2-m to an alpha-helix-containing aggregation-prone amyloidogenic conformer and subsequent amyloid fibril formation in vitro, the biological molecules with similar activity under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…Several groups have established conditions under which ␤2-m amyloid fibril formation occurs at a neutral pH (5)(6)(7)(8)(9)(10)(11). We found that ␤2-m amyloid fibrils are formed at a neutral pH in the presence of SDS (11).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Several groups have established conditions under which ␤2-m amyloid fibril formation occurs at a neutral pH (5)(6)(7)(8)(9)(10)(11). We found that ␤2-m amyloid fibrils are formed at a neutral pH in the presence of SDS (11).…”
mentioning
confidence: 75%
“…SDS is an anionic detergent that mimics some characteristics of biological membranes and is considered to be a good model for anionic lipids. We recently reported that some lysophospholipids, especially lysophosphatidic acid as well as nonesterified fatty acids induce the extension of ␤2-m amyloid fibrils at a neutral pH by partially unfolding the compact structure of ␤2-m to an amyloidogenic conformer as well as by stabilizing the extended fibrils (6,8). Although many groups have proposed the mechanisms by which ␤2-m amyloid fibrils are formed under physiological conditions, the biological machineries to inhibit the formation and deposition of ␤2-m amyloid fibrils are poorly understood (12).…”
mentioning
confidence: 99%
“…Fatty acids, such as palmitic acid, stearic acid, and oleic acid have been reported to be present in the serum in a molar ratio of 3:1:3 (2,27,28), and the mixture of these fatty acids is known to promote the amyloid fibril formation of ␤2m (7). In the present study, we have investigated the effect of the extracellular protein haptoglobin (Hp2-2 isoform) on the fatty acid-promoted de novo fibril formation of ␤2m.…”
mentioning
confidence: 99%
“…Therefore, understanding the factors (especially from plasma) that modulate the amyloid fibril formation of ␤2m is important in the context of ␤2m amyloidosis. Fatty acids, lysophospholip-ids (1,7,8), glycosaminoglycan, and proteoglycan are among the factors that are known to promote the fibril formation of ␤2m (9 -11). The details of plasma factors that suppress or inhibit the fibril formation are not completely understood.…”
mentioning
confidence: 99%
“…The structure of the N-terminal domain of ccd-Angptl4 appeared to be rather unstable. Several previous studies report that lipid-like compounds unfold proteins of different kinds to less structured states (52,53), probably because hydrophobic interaction is often central for protein packing.…”
Section: Proteinmentioning
confidence: 99%